2021
DOI: 10.1038/s41467-021-25928-2
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a more efficient prime editor 2 by addition of the Rad51 DNA-binding domain

Abstract: Although prime editing is a promising genome editing method, the efficiency of prime editor 2 (PE2) is often insufficient. Here we generate a more efficient variant of PE2, named hyPE2, by adding the Rad51 DNA-binding domain. When tested at endogenous sites, hyPE2 shows a median of 1.5- or 1.4- fold (range, 0.99- to 2.6-fold) higher efficiencies than PE2; furthermore, at sites where PE2-induced prime editing is very inefficient (efficiency < 1%), hyPE2 enables prime editing with efficiencies ranging from 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 37 publications
1
33
1
Order By: Relevance
“…1 a). Unlike the higher efficiency of DBD-integrated hyPE2 relative to PE2 in human cells [ 12 ], we found that phyPE2 conducted less efficient editing than pPE2 at the tested sites in rice (Fig. 1 c).…”
Section: Resultscontrasting
confidence: 66%
“…1 a). Unlike the higher efficiency of DBD-integrated hyPE2 relative to PE2 in human cells [ 12 ], we found that phyPE2 conducted less efficient editing than pPE2 at the tested sites in rice (Fig. 1 c).…”
Section: Resultscontrasting
confidence: 66%
“… 31 Moreover, several important progresses have also been made in enhancing the activity of prime editor itself. Equipping the prime editor with strong nuclear localization signal, 32 modifying the 3′ engineered pegRNA to reduce self-complementing 33 or degradation, 34 and enhancing the RT with ssDNA binding domain 35 were all capable of improving prime editing. It is, therefore, expectable that the introduction of these findings to WT-PE system may also increase its editing efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a fusion of the Rad51 DBD allowed editing of target sites that could not be edited using conventional base editors in rice ( Xu et al, 2022 ). Since the Rad51 DBD is a non-sequence-specific protein, it has also been used to stabilize the ssDNA and improve the efficiency in the Primer Editor (PE) system ( Song et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of the human Rad51 with the Cas9 (D10A) nickase successfully mediated recombination by the homology-directed repair (HDR) pathway ( Rees et al, 2019 ). The Rad51 N-terminal domain contains 114 residues involved in DNA binding ( Aihara et al, 1999 ) and several groups have successfully used this domain with CBEs and prime editors (PEs) to improve editing efficiency and expand the editing window ( Zhang et al, 2020 ; Song et al, 2021 ). Fusion of the Rad51 DBD with the Nmcas9-based CBE, termed hyper CBE (hyCBE), has proven successful in rice.…”
Section: Introductionmentioning
confidence: 99%